(untitled) (Bangladesh Journal of Nutrition, 2020)
Inadequate dietary diversity of adolescent girls has long been a problem in Bangladesh which contributed to the high prevalence of undernourishment among adolescent girls. Regardless of the socio-economic condition, the majority of the adolescent girls’ diet belongs to least diverse groups compared to other members of the households. Moreover, there is a lack of evidence on the determinants of this inadequate diversity. This review aims to identify these determinants using COM-B (capability, opportunity, motivation, and behavior) model. Eight databases and other sources were searched, and after removing irrelevant literature, 18 articles and reports were included to identify and categorize determinants in three components (capability, opportunity, and motivation) of COM-B model. The evidence revealed that the most important determinants of adolescent girls’ inadequate dietary diversity are: food insecurity and market availability of varieties of foods (determine the physical opportunity and capacity of girl and their households);lack of knowledge and awareness (the main driver of psychological capacity and motivations to have diverse diet); and pro-male socio-cultural and gender norms (limit girl’s social opportunity and reflectively motivate household members to curb girl’s accessibility to varieties of nutritious foods).Most of the determinants interact with each other to make complex nexus, making it difficult even for adolescent girls from wealthy and educated households to meet their nutritional demands by availing varieties of foods. Especially, socio-cultural and gender norms interfere with each determinant, making the adolescent girl’s more vulnerable to inadequacy. Comprehensive multi-component programs and interventions are imperative, which not only remove the external factors related to the physical opportunity of having diverse foods but also abolish the attitude-behaviour gap by creating the conducive socio-cultural environment or adolescent girls. Bangladesh J. Nutr. Vol. 33, December 2020, P: 29-43